Exploring disease perception and experiences of postoperative patients with Stanford type A aortic dissection: a qualitative study - Shuangdui Ji; Donglian Zheng; Shilin Ma; Shuping Guo; Fuzhen Ma; Changqi Yin; Guangli Mi (BMC Cardiovascular Disorders)
Abstract Background Stanford type A aortic dissection (TAAD) is a critical cardiovascular emergency characterized by acute onset, rapid progression, severe clinical manifestations, high mortality rates, and frequent complications. Patient’s postoperative experiences are closely linked to their physical and mental health. Therefore, understanding their illness experience is essential to facilitate recovery. Objective This study aimed to explore disease perception and postoperative experience of TAAD patients through semi-structured interviews, providing a formulation for developing standardized postoperative management protocols. Methods A phenomenological qualitative study was conducted in the cardiac and vascular surgery department of a tertiary hospital in Ningxia Hui Autonomous Region between January and May 2023. Purposive sampling was used to recruit postoperative TAAD patients. Semi-structured interviews were conducted to explore disease perception and experiences. Interview data were analyzed using Colaizzi’s seven-step analysis. Results A total of 16 patients were interviewed. Based on the interview data, 296 codes were extracted and pooled into 17 subthemes, which were finally integrated into 4 themes related to disease perception and experiences: significant symptom burden, complex and varied psychological experiences, different coping styles, and diverse needs for health services. Conclusion Postoperative TAAD patients face numerous health challenges. Healthcare providers should closely monitor physical symptoms, systematically address psychological fluctuations, develop targeted interventions based on identified coping patterns, and design patient-centered care models to address unmet needs. These strategies may alleviate adverse experiences and enhance rehabilitation outcomes.